Hiking during the COVID-19 pandemic: Demographic and visitor group factors associated with public health compliance. (27th May 2022) - Harris, Brandon; Rigolon, Alessandro; Fernandez, Mariela
Abstract: During the COVID-19 pandemic, compliance with public health guidelines to reduce the coronavirus spread became a focal point for park managers. Because parks were among the few spaces open to the public during the pandemic, park users may have been willing to accept the risk of noncompliance in exchange for the benefits of being outdoors. In this study, we used the SOPARC observation method to examine what predicted hikers' compliance with public health guidelines (social distancing or wearing a face mask) during the early stages of the COVID-19 pandemic. Noncompliance was associated with being a teenager or young adult and hiking before the Centers for Disease Control and Prevention (CDC) released the initial public health guidelines to prevent the spread of COVID-19. These findings contribute to the literature on noncompliance and risk-taking in parks and protected areas and have implications for parks and public health officials.